Immigrant Associations, Cultural Reproduction, and Agency among Indigenous Mexican Immigrants in the United States - Rivera-Salgado, Gaspar; Escala Rabadán, Luis (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2020)
In this paper, we examine the role of indigenous Mexican immigrant associations in California, United States, based on cultural preservation, with the aim of showing the organizational capacity of immigrant communities. Our research focused on the cultural festivals carried out by several immigrant associations in different cities in California. On the one hand, we assess the importance of cultural activities in the consolidation of immigrant communities in their places of destination. On the other, the enactment of these practices also exhibits the collective capacity of these communities through their associations, despite the indigenous and migrant condition of their membership, who usually cope with the worse social and labor conditions, and support their cultural activities with funds provided by their own membership and communities. We conclude that this study contributes to appreciate the relevance of the cultural dimension in the analysis of migrations.